Global public health a new era. - Beaglehole, R.; Bonita, R. (Oxford : Oxford University Press, 2009)
This edition addresses three major issues: the changing global context for public health; the state of public health practice in developed and developing countries; and strategies for strengthening the practice of public health in the 21st century.
Previous ed.: 2003.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Public health; Public health administration; Medical policy